Awake Tracheal Intubation Practice and Clinical Decision-Making in Brief Airway Scenarios Among Anesthesiologists in Türkiye: A Cross-Sectional Survey - Engin Çetin; Ahmet Yuksek (Farabi Tıp Dergisi, 2026)
Objective: Awake tracheal intubation (ATI) is recommended for an anticipated difficult airway, yet its use remains limited. This study evaluated anesthesiologists’ ATI practices and scenario-based decision-making and identified factors associated with its use.Material and Methods: This cross-sectional, convenience-sampled online survey was conducted in Türkiye (13 March–13 April 2026). Anesthesiology residents and specialists completed an anonymous questionnaire covering demographics, three brief clinical scenarios (anticipated difficult airway, emergency, low cooperation), perceived barriers (a study-specific barrier score), and attitudes and practices. The primary outcome was self-reported performance of ATI at least once within the previous year; secondary outcomes were scenario-based decision-making, overall frequency, associated factors, and perceived barriers. Multivariable logistic regression explored associated factors (N = 302).Results: Among 302 respondents, 30.8% reported performing ATI at least once within the previous year, and only 3.0% did so frequently or very frequently. In the anticipated difficult airway scenario 70.2% selected ATI. In the emergency scenario 51.7% preferred ATI. In the low-cooperation scenario 10.6% expressed a definite preference. Response formats differed across scenarios, so these proportions are not directly comparable. Respondents reporting ATI practice had lower barrier scores. In multivariable analysis, greater clinical experience was associated with higher odds of ATI practice, whereas state-hospital employment and a higher barrier score were associated with lower odds.Conclusion: Self-reported ATI practice was limited and showed scenario-specific response patterns. Greater clinical experience, lower perceived barriers, and institutional setting were associated with reported practice and may inform future training and institutional strategies; the cross-sectional, convenience-sampled design precludes causal inference.